Integrating Oceanographic Variability and Small-Scale Fishers’ Local Ecological Knowledge for Sustainable Fishing Ground Management in Eastern Indonesian Waters - Rizal Aidil; Aisyah Najwa (Journal of Community Action, 2026)
This study analyzes the integration of oceanographic variability and small-scale fishers’ local ecological knowledge (LEK) for sustainable fishing ground management in Eastern Indonesian waters. The region is characterized by strong seasonal dynamics driven by monsoonal systems, sea surface temperature fluctuations, and productivity shifts that influence fish distribution patterns. These environmental conditions create highly dynamic fishing grounds that are difficult to predict using conventional scientific models alone. A systematic synthesis of interdisciplinary literature was conducted, focusing on fisheries oceanography, LEK, and adaptive management frameworks. The analysis shows that oceanographic variables such as chlorophyll-a concentration, sea surface temperature, and ocean currents strongly determine the spatial distribution of pelagic fish stocks. However, fishers’ LEK provides complementary fine-scale information based on long-term ecological observation, including environmental cues such as water color, wind patterns, bird activity, and lunar cycles. Oceanographic data provides macro-scale predictive capacity, while LEK offers micro-scale contextual accuracy. Their integration improves fishing ground identification, enhances decision-making, and reduces uncertainty in data-limited fisheries. The study concludes that hybrid knowledge systems are essential for strengthening sustainable fisheries governance in Eastern Indonesia. Integrating scientific oceanographic analysis with LEK supports adaptive management, improves ecological resilience, and enhances livelihood sustainability in small-scale fisheries.